2004
DOI: 10.1111/j.1440-1770.2004.00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the toxicity of chemically fractionated Hamilton Harbour (Lake Ontario) sediment using selected aquatic organisms

Abstract: Studies of the sediments of Hamilton Harbour, Lake Ontario, Canada, have shown variable degrees of pollution with a large number of organic and inorganic pollutants. Three areas in the Harbour -Windemere Basin, Cootes Paradise and Randle Reef -exhibited particularly high levels of contaminants, with concomitant impacts on benthic organisms. Sediment samples examined in this study were taken from a site in Randle Reef in Hamilton Harbour and a station (LE 23) in Lake Erie used as a reference sample. The samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Hyalella azteca are freshwater amphipods extensively used to test acute and chronic toxicity of aquatic contaminants, especially in sediment toxicology testing due to their close association with sediments (Nebeker et al, 1986;Mackie, 1989;Borgmann et al, 1991;Phipps et al, 1995;McCarthy et al 2004;Wang et al, 2004;Ingersoll et al, 2005). An added benefit to using Hyalella is that they are prolific and rather hardy; thus, they are easy to culture and their results also generate less false positives than Daphnia.…”
Section: Hyalella Aztecamentioning
confidence: 99%
“…Hyalella azteca are freshwater amphipods extensively used to test acute and chronic toxicity of aquatic contaminants, especially in sediment toxicology testing due to their close association with sediments (Nebeker et al, 1986;Mackie, 1989;Borgmann et al, 1991;Phipps et al, 1995;McCarthy et al 2004;Wang et al, 2004;Ingersoll et al, 2005). An added benefit to using Hyalella is that they are prolific and rather hardy; thus, they are easy to culture and their results also generate less false positives than Daphnia.…”
Section: Hyalella Aztecamentioning
confidence: 99%
“…Toxicity of chemically fractionated Hamilton Harbor (Lake Ontario, Canada) sediment using selected aquatic organisms was assessed (McCarthy et al, 2004). In another study, increases in sediment loads on aquatic ecosystems were shown to have implications for the conservation of littoral communities in sediment-impacted areas (Donohue and Irvine, 2004a).…”
Section: Sedimentsmentioning
confidence: 99%
“…High levels of contaminants in the sediment have also been associated with the restricted benthic macroinvertebrate community of the harbour (Krantzberg and Boyd, 1992). Polyaromatic hydrocarbons in Hamilton Harbour sediment were the cause of toxicity to four aquatic species in bioassays (McCarthy et al, 2004). However, persistent organic pollutant concentrations in the Great Lakes declined precipitously in the late 1970s, and, at a slower rate, have continued to stabilize or decline since that time (Pettit et al, 1994).…”
Section: Introductionmentioning
confidence: 96%